2020
DOI: 10.1038/s41598-020-59391-8
|View full text |Cite
|
Sign up to set email alerts
|

Association between uric acid and brachial-ankle pulse wave velocity: secondary analysis of data from a cross-sectional study

Abstract: At present, the association between uric acid (UA) and brachial-ankle pulse wave velocity (bapWV)has not been well clarified. This study is the second analysis based on a cross-sectional study. 912 participants (average age is 51.5 ± 9.6 years) who underwent medical health examinations were included in this study, UA levels and baPWV were measured. Participants were divided into four groups according to UA levels (Quantile 1: 2.00-4.10 mg/dL; Quantile 2: 4.20-5.20 mg/dL; Quantile 3: 5.30-6.00 mg/dL and Quantil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 43 publications
1
8
1
Order By: Relevance
“…shows that the left and right hands of the PWV parameter showed significant relation with high and normal UA which similar as reported in [11,12]. The PPG features showed that the onset to the systolic peak of left hand (LO1_S1) and onset to the dicrotic notch of the right hand (RO1_N1) of PPG in time domain is the most significant compared the three other fiducial points.…”
Section: Machine Learningsupporting
confidence: 84%
See 1 more Smart Citation
“…shows that the left and right hands of the PWV parameter showed significant relation with high and normal UA which similar as reported in [11,12]. The PPG features showed that the onset to the systolic peak of left hand (LO1_S1) and onset to the dicrotic notch of the right hand (RO1_N1) of PPG in time domain is the most significant compared the three other fiducial points.…”
Section: Machine Learningsupporting
confidence: 84%
“…A study on the correlation between UA and brachial-ankle pulse wave velocity (ba-PWV) was controversial [9,10]. However, a cross-sectional study from Japan population has shown a significant association between ba-PWV and UA with a p-value of less than 0.05 [11,12]. In addition to ba-PWV, machine learning (ML) is a promising tool in prediction and classification, especially in various applications in a clinical setup.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the mechanism, an increased RHR can change the viscoelasticity of the arterial wall, thus increasing arterial stiffness [43]. A study including 912 females showed that the urea acid level and baPWV had a positive nonlinear correlation [44], but our study showed that the level of urea acid was significantly linearly correlated with baPWV in females but not in males. In the previous literature, total homocysteine levels, BMI, low creatinine clearance, proteinuria, urine albumin, and salt intake were also reported to be associated with baPWV [22,38,45].…”
Section: Discussioncontrasting
confidence: 67%
“…Uric acid also promotes endothelial dysfunction through inactivation of NO and impairment of endothelial cells proliferation 46 . Moreover, urate crystals are deposited on the arterial wall, which causes inflammation, stimulates mast cells, induces lipid infiltration, and further destroys the intimal cells of the arteries, thereby blocking the metabolism of apolipoprotein B (apoB) and eventually leading to the aggravation of atherosclerosis 27 . Uric acid has a dual role, in addition to an oxidative effect, it also has an antioxidant effect 48 .…”
Section: Discussionmentioning
confidence: 99%